War and welfare : British prisoner of war families, 1939-45. - Hately-Broad, Barbara (Manchester University Press, 2009)
During the Second World War, some 250,000 British servicemen were taken captive by either the Axis powers or the Japanese. As a result of this, their wives and families became completely dependent on the military and civil authorities. This book examines the experiences of the millions of service dependents created by total war. The book then focuses on the most disadvantaged elements of this group - the wives, children and dependents of men taken prisoner- and the changes brought about by the exigencies of total war. Further chapters reflect on how these families organised to lobby government.